Carbetocin for the prevention of post-partum hemorrhage after vaginal birth: a real-world application. (12th December 2022) - Sichitiu, Joanna; Baud, David; Desseauve, David
Abstract: Objective: To compare maternal outcomes using Carbetocin versus Oxytocin for the active management of the third stage of labor, given a temporary national shortage of Oxytocin. Methods: We conducted a retrospective observational study on a cohort of 866 women with vaginal deliveries at our center, >36 weeks of gestation, between November 2018 and March 2019. During the shortage period, each woman received a single slow intravenous injection of Carbetocin 100 µg at delivery of the anterior shoulder, rather than Oxytocin 5 UI, as postpartum hemorrhage prophylaxis. 146 (16.9%) patients received Carbetocin versus 720 (83.1%) receiving Oxytocin. The outcomes were rates of postpartum hemorrhage, severe postpartum hemorrhage, and placental retention. Results: Incidence rates of placental retention and postpartum hemorrhage were 4.9% and 9.4% respectively. Placenta retention was significantly more likely following Carbetocin administration (adjusted odds ratio 2.5; 95% confidence interval 1.2–5.0). Postpartum hemorrhage rates were not significantly different (adjusted odds ratio 1.1; 95% confidence interval 0.6–2.1), as were severe postpartum hemorrhage rates (adjusted odds ratio 0.7; 95% confidence interval 0.2–2.2). Conclusion: Carbetocin is as effective as Oxytocin for postpartum hemorrhage prevention. However, we would reserve it for use after placental delivery due to the increased retention rates.